Flue‐Gas Desulfurization by Using a HiGee Electric‐Field Device. Issue 4 (6th March 2018) - Zou, Hai-Kui; Arowo, Moses; Zhang, Qiang; Zhang, Liangliang; Sun, Baochang; Chu, Guang-Wen; Shao, Lei; Chen, Jian-Feng
Abstract: An innovative technique to remove SO2 from flue gas, comprising a rotating packed bed (RPB) coupled with an electric‐field device, is presented herein. The effects of operating conditions, such as packing type, rotation speed, gas‐liquid volumetric ratio, Na2 SO3 content, and voltage supply on SO2 removal efficiency ( η ), as well as the gas‐phase overall volumetric mass‐transfer coefficient ( K G a ), were systematically investigated. Results indicate that a high η can be achieved under certain operating conditions. A correlation to predict K G a was also established and results show that the predicted values are in agreement with the experimental results. This work generally provides a feasible means of intensification for flue gas desulfurization. Abstract : SO2 is one of the major causes of acid rain and is mainly generated from coal combustion systems. SO2 is removed from flue gas by using a system composed of a rotating packed bed and an electric‐field device. The effects of operating conditions on SO2 removal efficiency and gas‐phase overall volumetric mass‐transfer coefficient are revealed.